PENERAPAN BLUD KPHP: AKANKAH MENUJU PENGELOLAAN HUTAN YANG TRANSPARAN, AKUNTABEL DAN PARTISIPATIF? - Pandriadi, Pandriadi; Wijaya, Angka; Amah, Mas (Fakultas Ekonomi Universitas IBA, 2017)
This resarch starts from the evidence that deforestation and degradation rate in MusiRawas District remain increase, particularly in KPHP Lakitan areas. Based on formerresearch, one of problem roots is governance. So that’s why this research aims to knowwether implementation of BLUD in KPHP Lakitan will make better governance in forestgovernance that may reduce the rate of deforestation and degradation. This research isqualitative research that tried to find data and information as much as possible by usingdeep interview and Focus Group Discussion (FGD). The informan in this research aregovernment staffs, poeple who stay in or suround the forest area, and business companies.The result shows that implementing BLUD on KPHP Lakitan may give room for KPHPLakitan to improve forest governance by using tranparancy, accountable, andparticipative concepts, therefore this is potentially to reduce the rate of deforestation anddegradation in KPHP Lakitan’s areas.